Effect of Substrate and Water on Cultivation of Sumba Seaworm (Nyale) and Experimental Practicum Design for Improving Critical and Creative Thinking Skills of Prospective Science Teacher in Biology and Supporting Sustainable Development Goals (SDGs) - Kerans, Geterudis; Sanjaya, Yayan; Liliasari, L.; Pamungkas, Joko; Ate, Yustinus Ghanggo (Universitas Pendidikan Indonesia (UPI), 2024)
This research aims to determine the effect of substrate and water type on the cultivation of Sumba seaworm (Nyale) and develop an authentic inquiry project-based practicum instrument on Nyale as Polychaeta to improve critical and creative thinking skills of prospective science teachers. The results of experimental research showed that the substrate of sea sand and sea coral can be used in Nyale cultivation because it can provide a higher survival rate for this organism. Cultivation without substrate causes Nyale to survive less. Sea water is needed to be used in cultivation. The development of an authentic inquiry project practicum instrument about Nyale shows that the instrument is feasible to be used in practicum to improve the critical and creative thinking skills of prospective science teachers. This research contributes well to the development of authentic science learning that can create meaningful science learning for students. This research also supports a problem solver for current issues in the sustainable development goals (SDGs).